Studies on the impact of conventional and hermetic storage techniques on the paddy quality: Hermetic bag: An efficient way of storing paddy - Sivashankari, M; Khandai, suryakanta (ORYZA-An International Journal of Rice, 2025)
Paddy storage, a vital practice in agriculture, ensures the preservation of harvested rice grains by managing key factors such as humidity, temperature, and cleanliness. This study compared the effects of hermetic and traditional storage methods on the qualitative attributes of Swarna, a widely cultivated paddy variety. After harvest, paddy samples were dried to a moisture content of 12.1% (w.b) and stored in IRRI hermetic super bags and traditional gunny bags under ambient conditions (30.5°C temperature and 82% relative humidity). The quality of the stored paddy was monitored over a six-month period. The results revealed that paddy stored in traditional gunny bags suffered from pest infestation, leading to significant degradation in quality. This was evident through low germination rate of 68.2%, making the paddy unsuitable for seed production. In contrast, paddy stored in IRRI hermetic super bags showed no signs of insect infestation and maintained a stable moisture level throughout the storage period. Consequently, the germination rate for seeds stored in hermetic bags was significantly higher (91.7%), indicating superior preservation of seed quality. The findings suggest that IRRI hermetic super bags are more effective than traditional storage methods, particularly in maintaining moisture levels, preventing pest damage, and preserving the viability of paddy seeds (p<0.05). The adoption of hermetic storage methods, a green alternative for storing paddy, could greatly benefit rural farmers by minimizing post-harvest losses. This can be achieved through farmer training and demonstrations, encouraging the widespread use of this improved storage technology.